Mikro-, małe i średnie przedsiębiorstwa — remedium na bezrobocie wśród absolwentów - Januszewska, Małgorzata J. (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
This article presents to the reader the situation of Polish graduates, in particular with regards to the problem of unemployment. It shows the scale of the problem and suggestions for ways to deal with the lack of work. It also discusses the size and role of the MSMEs in eliminating unemployment. For this purpose, it explains the procedure of establishing enterprises and lists institutions providing money for start-ups. The article questions the effectiveness of this method. In the following part it discusses the role of informed choice between different kinds of high schools in reducing the level of unemployment among graduates. Finally, it also questions the value of a master’s degree. The author states that there is a mismatch between the structure of education and the needs of the market.
Keywords: graduate; unemployment; education; maladjustment to market needs; craftsmen; MSME sector